A trajetória do discurso do desenvolvimento para o Nordeste : políticas públicas na (dis)simulação da esperança. - Lisboa, Josefa Bispo de (2007)
This study is centered in the ideologic speech of the implied development in the public politics of regional development of Northeast. To be apprehended in the contradictory relationships of the capital space. In this way, the economical growth is understood as nucleus founder of this ideology. As initial reflection, the fundamental presuppositions of the development are retaken, investigating the possibility of balance of the world capitalist economy through the overcoming of the disagreements of the underdevelopment. It was investigated with base in the reading of the social thought on the Northeast, the functional sense of the regional subject for the insert of that area in the capital circuit. The understanding of the speech of the development starting from 1980 addressed a reflection on the historical-social process that makes the World Bank the key institution of the structural adjustment and its transmitter paper of the ideology of the maintainable local development expressed in the use of the territory for the capitalist exploration as manifestation of the regional development. It was verified, with base in field research, the registration of the public politics financed by the Programa de Combate à Pobreza Rural in the states of Ceará, Pernambuco and Sergipe, while condition of appropriation of the territory in the use of the poverty as useful rhetoric to the continuity of the production model. Engendered by the mundialization of capital, the local dimension brings the dynamic character of the territory, sustained in the idea of latent potentiality. The places become interesting, attractive and useful to the accumulation and guarantee the capital mobility. The speech of the development, far away from being a subject of the illusory character while accomplishing an important ideological function: the legitimation of capitalist production relationships that operates the differences, or, in other words, drive the poverty production. Starting from the inclusion of the speech path of the development for the Northeast in socialmetabolic relationships of the capital, Geography has, in its role, the paper of watching the unequal and combined character of the development, corroborating for the elucidation and overcoming the contradictions.